Three-year observations on the effect of different cusp inclinations on the restoration of short maxillary first molar implants: A randomized controlled trial - Cheng, Yuye; Xiao, Cong; Zhu, Yu; Chen, Qiuyan; Zhang, Longbo; Zhang, Yanshu; Gao, Meiqin; Li, Xinpei; Zhou, Yan; Song, Guiqiang; Zhang, Tiecheng; Pei, Runsheng (Frontiers in Physiology, 2023)
Objective: To investigate the effect of different cusp inclination on short implant prosthesis of maxillary first molar after 3 years of load bearing in biology and mechanics. Methods: The clinical patients were randomly selected from the database and divided into four groups A, B, C, and D according to the cusp angle of the maxillary first molar short implant restoration (4.8*8mm, Dentium). 20 cases in each group. The cusp inclination was 10 ° ~ 15 °, 15 ° ~ 20 °, 20 ° ~ 25 °, 25 ° ~ 30 °. After 3 years of weight-bearing, cone beam computed tomography ( CBCT ) and Florida probe were used to measure and observe the height of alveolar bone ( H ), periodontal probing depth ( PD ) and modified sulcus bleeding index ( MBI ). Visual analogue scale ( VAS ) was used to evaluate the overall satisfaction of patients, and the mechanical complications of each group within 3 years of implant weight-bearing were counted. Results: the H and PD of group D were 1.09 ± 0.23 and 2.19 ± 0.11 respectively, which were significantly higher than those of group A, B and C (P<0.05).; There was no significant difference in MBI between groups A ~ D (P>0.05). The VAS scores of group B and group C were 88.36 ± 5.12 and 88.70 ± 4.52 respectively, which were higher than those of group A and group D (P<0.05). The incidence of food impaction, porcelain collapse and abutment loosening in group D were 40.0 %, 25.0 % and 15.0 % respectively, which were higher than those in group B and C (P<0.05). Conclusion: The risk of biological and mechanical complications increases after long-term weight-bearing of maxillary first molar short implant prostheses with high cusp inclination. The cusp inclination of short implant prostheses should be designed as low as 25 °.